Originally Posted by

**Tweety** I dont really understand what you did, aren't you meant to prove that $\displaystyle c^{2} = \frac{16}{a^{2}-16} $? Why are you doing $\displaystyle c^{2} = cot^2{x} $?

This is what I have done but it does not fall together!

$\displaystyle c = cotx , c^{2} = cot^{2}x $

$\displaystyle b = \frac{4}{a} , b^{2} = \frac{16}{a^{2}} $

$\displaystyle cos^{2}x = \frac{16}{a^{2}} $

$\displaystyle 1-sin^{2}x = \frac{16}{a^{2}} $

$\displaystyle a^{2}(1-sin^{2}x) = 16 $

$\displaystyle a^{2} = \frac{16}{1-sin^{2}x} $

$\displaystyle a^{2} = \frac{16}{1} - \frac{16}{sin^{2}x} $ this step is incorrect ... you cannot "split" the denominator like that.